A Review of Acute Aerobic Exercise and Transcranial Direct Current Stimulation Effects on Cognitive Functions and Their Potential Synergies - Steinberg, Fabian; Pixa, Nils Henrik; Fregni, Felipe (Frontiers in Human Neuroscience, 2019)
Today, several pharmaceutic and non-pharmaceutic approaches exist to treat psychiatric and neurological diseases. Because of the lack of treatment procedures that are medication free and the lack of severe side effects, transcranial direct current stimulation (tDCS) and aerobic exercise (AE) have been tested to explore the potential for initiating and modulating neuroplasticity in the human brain. Both tDCS and AE could support cognition and behavior in the clinical and non-clinical context to improve the recovery process within neurological or psychiatric conditions or to increase performance. As these techniques still lack meaningful effects, although they provide multiple beneficial opportunities within disease and health applications, there is emerging interest to find improved tDCS and AE protocols. Since multimodal approaches could provoke synergetic effects, several recent studies have begun to combine tDCS and AE within different settings such as in cognitive training in health or for treatment purposes within clinical settings, all of which show superior effects compared to single technique applications. The beneficial outcomes of both techniques depend on several parameters and the understanding of neural mechanisms that are not yet fully understood. Recent studies have begun to directly combine tDCS and AE within one session, although their interactions on the behavioral, neurophysiological and neurochemical levels are entirely unclear. Therefore, this review a) provides an overview of acute behavioral, neurophysiological, and neurochemical effects that both techniques provoke within only one single application in isolation; b) gives an overview regarding the mechanistic pathways; and c) discusses potential interactions and synergies between tDCS and AE that might be provoked when directly combining both techniques. From this literature review focusing primarily on the cognitive domain in term of specific executive functions (inhibition, updating, and switching), it is concluded that a direct combination of tDCS and AE provides multiple beneficial opportunities for synergistic effects. A combination could be useful within non-clinical settings in health and for treating several psychiatric and neurologic conditions. However, there is a lack of research and there are several possibly interacting moderating parameters that must be considered and more importantly must be systematically investigated in the future.